Removal of Cd2+ and Cu2＋ by free and immobilized saccharomyces cerevisiae: kinetic and equilibrium modeling - Martins, Ramiro (2010)
Removal of Cd2+ and Cu2＋ by free and immobilized Saccharomyces cerevisiae: kinetic and equilibrium modeling.